Udveksling og gave i det fjerde eu-angelium og dets dys-angelium: eksegese af Joh 3,16 - Nielsen, Jesper Tang (Dansk teologisk tidsskrift, 2016)
Resumé This article is a tribute to Ole Davidsen on the occasion of his retirement from the University of Aarhus. Theories of gift-giving and exchange have been an important factor for Davidsens interpretation of New Testament theology and recently for his understanding of the Gospel of John. I present Davidsens semiotic formulation of the conceptual frame constituted by giving and taking and his understanding of the fundamental New Testament structures. Davidsen insists that the Gospel of John involves a sacrificial understanding of the death of Jesus. He argues that God gives his son in order to repay for an illegitimate take. Therefore he proposes an Adam-myth as background for the Gospel of John. This view is challenged in the article. I argue on the basis of an exegesis of John 3:16 that the illegitimate take consists in a lack of recognition of God, i.e. a degressive cognitive act. That is the underlaying dys-angelium to which the Johannine eu-angelium responds. The gift in the Gospel of John is recognition of God brought forth by Jesus, i.e. a progressive cognitive act.